2020
DOI: 10.3390/molecules25225357
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Digestibility of Soybean, Fish, and Microalgal Oils, and Their Influences on Fatty Acid Distribution in Tissue Lipid of Mice

Abstract: The digestion rates of microalgal (docosahexaenoic acid, DHA, 56.8%; palmitic acid, 22.4%), fish (DHA, 10.8%; eicosapentaenoic acid, EPA, 16.2%), and soybean oils (oleic, 21.7%; linoleic acid, 54.6%) were compared by coupling the in vitro multi-step and in vivo apparent digestion models using mice. The in vitro digestion rate estimated based on the released free fatty acids content was remarkably higher in soybean and fish oils than in microalgal oil in 30 min; however, microalgal and fish oils had similar dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This finding was corroborated by the lower fat digestibility (78%) observed in senior cats when fed the HF-LFb diet, which contained a similar total fat level than the HF-MFb (17-18%) but from different ingredient sources. Although fish oil, rich in polyunsaturated fatty acids (PUFA), was the main fat source in the HF-LFb diet, certain PUFA may have a lower hydrolysis rate [35], which is related to the location of the double bond and molecular structure [36].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was corroborated by the lower fat digestibility (78%) observed in senior cats when fed the HF-LFb diet, which contained a similar total fat level than the HF-MFb (17-18%) but from different ingredient sources. Although fish oil, rich in polyunsaturated fatty acids (PUFA), was the main fat source in the HF-LFb diet, certain PUFA may have a lower hydrolysis rate [35], which is related to the location of the double bond and molecular structure [36].…”
Section: Discussionmentioning
confidence: 99%
“…Molecules 2021, 26, x FOR PEER REVIEW 2 of 13 acid and 21.2% oleic acid) or lard (45.1% oleic acid and 26.5% palmitic acid) without affecting their daily food intake [8]. Additionally, body weights of mice that consumed a high fat diet containing microalgal oil (56.8% DHA, 22.4% palmitic acid) were significantly decreased compared with the mice that consumed fish oil [9]. Du et al conducted a metaanalysis of randomized controlled trials and found that fish oil supplementation may help reduce abdominal fat [10].…”
Section: Preferential Consumption Of High-fat Diets Composed Of Diffe...mentioning
confidence: 99%
“…For example, mice who consumed a high-fat diet containing Spirulina lipids (46.8% palmitic acid, 20.3% γ-linolenic acid, and 16.8% linoleic acid) or fish oil (26.6% docosahexaenoic acid [DHA], 14.3% eicosapentaenoic acid [EPA], and 14.4% palmitic acid), gained less weight than mice consuming the same amount of a high-fat diet composed of soybean oil (54.5% linoleic acid and 21.2% oleic acid) or lard (45.1% oleic acid and 26.5% palmitic acid) without affecting their daily food intake [8]. Additionally, body weights of mice that consumed a high fat diet containing Molecules 2022, 27, 1271 2 of 12 microalgal oil (56.8% DHA, 22.4% palmitic acid) were significantly decreased compared with the mice that consumed fish oil [9]. Du et al conducted a meta-analysis of randomized controlled trials and found that fish oil supplementation may help reduce abdominal fat [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among FAs, short-chain FAs (4~6 carbons in chain length) are most rapidly broken down by pancreatic lipases, followed by long-chain/unsaturated FAs and saturated FAs [ 9 ]. Based on the apparent digestibility of individual FAs following the administration of soybean oil to mice, the digestibility of P (88.43%) was higher than that of S (85.87%) in saturated FAs ( p < 0.05), while the digestibility of linolenic acid (96.2%) was the highest in unsaturated FAs, followed by those of linoleic acid (93.63%) and oleic acid (91.53%) ( p < 0.05) [ 11 ]. The in vivo absorption rates of the OPO and OOP diets in rats have been reported to be 80% and 67%, respectively, and as an individual FA, the absorption rates of P in the administrated OPO and OOP are 80% and 63%, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on analyzing the physicochemical properties of TAGs that differ in the regiospecific positions of certain FAs [ 13 , 14 , 15 , 16 , 17 ]. Previous studies on lipid digestibility have measured and compared the relative digestion rates of edible oils (soybean oil, algae oil, DAG-rich algae oil) [ 18 ] and symmetrical or non-symmetrical TAGs based on the levels of hydrolyzed FFAs using the in vitro digestion method [ 19 ] or compared in vivo digestion rates of specific edible oils using animal models [ 11 ]. However, studies comparing the digestion characteristics of lipids containing TAGs with different types of FAs (such as P, O, or S) and the incorporated positions of the FAs are still limited.…”
Section: Introductionmentioning
confidence: 99%